The Influence of Health Education on Adolescents' Knowledge of Promiscuity at SMK Negeri 1 Limboto - Rini Asnawat; Nirmala Sunati; Syabirin B. Syukur; Suci Setiawati A. Karim; Nabila Shabrina Hantai; Natasya Fadillah Irwadin; Sri Nurain I. S. Daduke; Rita Tamrin; Sultan Rizki Polamolo; Andi Azkia Musdalifah; Fidya Anggriani Adam; Suci Fitri Mutia Bagu; Sri Wanda Wante; Isnawati Usman; Magfira Gobel; Tiyansi S. Muko; Maimuna Paneo; Paramudita Podu; Susandri Kango; Fachrul Alfaridzi Rahim; Nur Hayun Oktaviany; Dwy Venia Hulalata; Alfiah Aprilia Musa; Nur Fadilah Eraku; Fitra Juniarty Nusi; Mutiara K. Hasan; Inriyanti Tui; Nurhaliza Ihwan; Adinda Ramadani Helingo; Fitaloka Dukalang; Delima Suleman; Rahmat Hamsah; Mulyadi Basole; Wahyu Saputra Tobuhu; Ariansyah Batalipu; Mohamad Julianda Kantu; Gina Raudatul Janna Karim (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Introduction: Promiscuity in adolescents is a complex public health problem and has the risk of causing unwanted pregnancies, sexually transmitted infections (STIs), HIV/AIDS, and mental health disorders. SMK Negeri 1 Limboto has never received a structured reproductive health education program. This study aims to analyze the influence of health education carried out by the 2023 Nursing Class C team of the University of Muhammadiyah Gorontalo on increasing adolescents' knowledge about promiscuity. Methods: This study used a pre-experimental design with a one group pre-test post-test approach. The sample amounted to 100 students in grades X and XI of SMK Negeri 1 Limboto who were selected using the purposive sampling technique. The intervention was in the form of health counseling for 3 hours using the ppt presentation method and a question and answer session and simulation. The implementers of the activity are 34 students of Class C Nursing with a division of duties according to POAC management. The instrument used a structured questionnaire that had been tested for validity and reliability (Cronbach's Alpha = 0.87). Data analysis was conducted using a paired t-test with α = 0.05. Results: The average pre-test students' knowledge was 55.4 (SD = 12.6) and after the intervention (post-test) increased to 85.2 (SD = 8.3) with an increase of 29.8 points. All 100 students (100%) were present from the beginning to the end of the activity. The results of the paired t-test showed a p value of < 0.001 (p < 0.05), which means that there was a significant difference between the knowledge before and after the counseling. As many as 90% of students achieved a score of ≥75 on the post-test compared to only 14% on the pre-test. Other findings showed that 36% of students had been invited to drink alcohol, 14% had been invited to try drugs, and 68% were uncomfortable telling their parents/teachers. Conclusion: The health education carried out by the 2023 Nursing Class C team (34 people) using the POAC approach was effective in increasing adolescents' knowledge of promiscuity with a perfect participation rate (100%). This program is recommended to be implemented in an ongoing manner in schools.